2000
DOI: 10.1021/jp992963u
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Intramolecular Charge Transfer after Local Two-Photon Ionization of Ferrocene Derivatives with Aromatic Chromophores

Abstract: Experimental evidence for dissociative intramolecular charge transfer processes is found for gas-phase ferrocene-aniline derivatives after local ionization at the aniline chromophore site via intermediate states with predominant aniline character. The direct ionization at the ferrocene site can be excluded since there is a rapid dissociation of ferrocene in the intermediate state prior to ionization so that no ferrocene ions would be produced in this case. Because of the higher local ionization energy of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…The nanosecond mass spectra measured in this work at laser frequencies above 40 700 cm -1 (Figure ) are completely different from the spectra reported earlier, which revealed only the Fe + peak. However, comparing the mass spectra recorded in the lower-energy and higher-energy regions (Figures and ) shows that the intensity of the Cp 2 Fe + ion signal remains practically unchanged.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The nanosecond mass spectra measured in this work at laser frequencies above 40 700 cm -1 (Figure ) are completely different from the spectra reported earlier, which revealed only the Fe + peak. However, comparing the mass spectra recorded in the lower-energy and higher-energy regions (Figures and ) shows that the intensity of the Cp 2 Fe + ion signal remains practically unchanged.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies of ferrocene cooled in a supersonic jet with the use of nanosecond tunable laser pulses in the 235−285 nm range have also revealed only iron ions in the mass spectra. Under optimal conditions, very small amounts of CpFe + ( m / z = 121) and Cp 2 Fe + ( m / z = 186) with intensities of less than 1% relative to that of the base peak Fe + ( m / z = 56) have been found .…”
Section: Introductionmentioning
confidence: 99%
“…Multiphoton dissociation of many metallocene compounds has been studied by mass spectroscopy. [16][17][18][19][20][21][22][23][24][25][26][27] The wavelength dependence of the total ion current spectrum for ferrocene and cobaltocene in the ranges 366-370, 380-390, and 445-455 nm and for nickelocene in the range 375-520 nm was reported. 20,24,25 The features in the excitation spectrum were attributed solely to the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by the help of DFT calculations, Rodionov's group has found that under ESI conditions the initial ferrocene derivative molecules were oxidized by the protonated ones to form molecular ions . It is sound to propose that ferrocene‐containing substances are facile to participate in redox processes in the gas phase as they do in the solid and liquid phase . A schematic potential energy surface of the model compound benzoylferrocene is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[10,11] It is sound to propose that ferrocene-containing substances are facile to participate in redox processes in the gas phase as they do in the solid and liquid phase. [5,24] A schematic potential energy surface of the model compound benzoylferrocene is given in Fig. 3 to quantitatively describe the energy requirement of these reactions.…”
Section: Single Electron Redox By Ion-neutral Complexesmentioning
confidence: 99%